Transcriptional analysis of microRNAs related to unsaturated fatty acid synthesis by interfering bovine adipocyte ACSL1 gene - Li, Xupeng; Bai, Yanbin; Li, Jingsheng; Chen, Zongchang; Ma, Yong; Shi, Bingang; Han, Xiangmin; Luo, Yuzhu; Hu, Jiang; Wang, Jiqing; Liu, Xiu; Li, Shaobin; et al. (Frontiers in Genetics, 2022)
Long-chain fatty acyl-CoA synthase 1 (ACSL1) plays a vital role in the synthesis and metabolism of fatty acids. The proportion of highly unsaturated fatty acids in beef not only affects the flavor and improves the meat’s nutritional value. In this study, si-ACSL1 and NC-ACSL1 were transfected in bovine preadipocytes, respectively, collected cells were isolated on the fourth day of induction, and then RNA-Seq technology was used to screen miRNAs related to unsaturated fatty acid synthesis. A total of 1,075 miRNAs were characterized as differentially expressed miRNAs (DE-miRNAs), of which the expressions of 16 miRNAs were upregulated, and that of 12 were downregulated. Gene ontology analysis indicated that the target genes of DE-miRNAs were mainly involved in biological regulation and metabolic processes. Additionally, KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis identified that the target genes of DE-miRNAs were mainly enriched in metabolic pathways, fatty acid metabolism, PI3K-Akt signaling pathway, glycerophospholipid metabolism, fatty acid elongation, and glucagon signaling pathway. Combined with the previous mRNA sequencing results, several key miRNA-mRNA targeting relationship pairs, i.e., novel-m0035-5p—ACSL1, novel-m0035-5p—ELOVL4, miR-9-X—ACSL1, bta-miR-677—ACSL1, miR-129-X—ELOVL4, and bta-miR-485—FADS2 were screened via the miRNA-mRNA interaction network. Thus, the results of this study provide a theoretical basis for further research on miRNA regulation of unsaturated fatty acid synthesis in bovine adipocytes.